Prognostic value of pulmonary blood volume by first-pass contrast-enhanced CMR in heart failure outpatients: the PROVE-HF study. (17th October 2017) - Ricci, F; Barison, A; Todiere, G; Mantini, C; Cotroneo, A R; Emdin, M; De Caterina, R; Galllina, S; Aquaro, G D
Abstract: Aims: Pulmonary blood volume (PBV) is a novel clinical application of cardiovascular magnetic resonance (CMR) imaging for the quantitative grading of haemodynamic congestion. In this study, we aimed to assess the prognostic value of PBV in a cohort of outpatients with chronic heart failure (HF). Methods and results: One hundred and twelve consecutive patients (91 men, 67 ± 12 years) and 53 age- and sex-matched healthy controls underwent echocardiography and contrast-enhanced CMR. PBV was calculated as the product of stroke volume and the number of cardiac cycles for an intravenous bolus of gadolinium contrast to pass through the pulmonary circulation determined by first-pass perfusion imaging. Compared with healthy controls, HF outpatients showed significantly higher PBV index (PBVI, 308 ± 92 vs. 373 ± 175, mL/m 2, P = 0.012) and pulmonary transit time (6.8 ± 1.8 vs. 9.5 ± 4 s, P ≤0.001). During a median follow-up of 26 ± 17 months, 27 patients (24%) reached the composite end point of cardiovascular death, HF hospitalization, or sustained ventricular arrhythmias/appropriate implantable cardioverter-defibrillator intervention. Using a cut-off point of PBVI >492 mL/m 2, corresponding to two standard deviations above the mean of healthy controls, event-free survival was significantly lower in patients with higher PBVI ( P < 0.001). At multivariable-adjusted Cox regression analysis, PBVI was an independent predictor of the composite cardiovascular end point (per 10% increase hazard ratio 1.31, 95% confidence interval: 1.02–1.69, P = 0.03). Conclusions: PBVI is a novel application of perfusion CMR potentially useful to quantitatively determine haemodynamic congestion as a surrogate marker of left ventricular diastolic dysfunction. PBVI might prove to be helpful in stratifying the prognosis of asymptomatic or mildly symptomatic patients with left ventricular dysfunction.